Explaining and predicting participation in adult education: A longitudinal study - Baiyin Yang (Adult Education Research Conference, 1995)
Few studies and theoretical frameworks have treated participation in adult education from a longitudinal perspective. This paper presents a model which posits that PAE is embedded in the adult developmental process and is the interactive result of individual internal and external forces. The model was tested on a national sampled data set.